Potential of Controlled Irrigation and Drainage for Reducing Nitrogen Emission from Rice Paddies in Southern China - Guang-cheng Shao; Ming-hui Wang; Shuang-en Yu; Na Liu; Meng-hua Xiao; Min Yuan (Journal of Chemistry)
The effect of controlled irrigation and drainage (CID) at different growth stages of rice on nitrogen (N) from rice paddy was studied. Submergence at different stages was imposed in specially designed experimental tanks in 2009 and 2010 based on alternate wetting and drying technology (AWD, the control, CK). Treatments include CID treatment at tiller stage (T1), jointing-booting stage (T2), panicle initiation stage (T3), and milky stage (T4). Results showed that fertilization could significantly increase the concentration of NH4+-N and TN in surface water but had a little influence on NO3--N. The concentrations of NH4+-N and NO3--N in surface water increased at first and then decreased after fertilization, while the concentrations of NH4+-N and TN in groundwater kept on being relatively stable. Compared to CK, CID significantly increased the concentration of NH4+-N in surface water at four stages. However, it reduced the concentration of NO3--N. Consistent with the reduction of drainage, CID at four stages could significantly decrease the amount of NH4+-N and NO3--N losses by runoff in relation to CK.